Faktor-Faktor Penentu Dalam Berbelanja Secara Online - Wijaya, Ronald Alexander; Sutapa, Nyoman (Jurnal Titra, 2014)
The development of the internet technology is currently utilized by user, one of them is an online business. This research is to find the factors which influence the consumers to buy through online shopping. The data is been analyzed with Factor Analysing and Discrimination Test. The results shows that there are four components constructed from Factor Analysis and the most influencing components are attractive web design, full information, ease to shop, and advertising media as a supporting facilites. Discriminant test shows that male at junior high school student and collage/university students more dominant at frequency never (0) and occasionally (1-3 times) in the last month, but at the senior high school female students are dominant at the occasionally frequency. Females shopping frequencies are dominant at medium frequency (4-6 times), but at high school degree both female and male have the same shopping frequency. The result of discriminant test also shows expenditures less than Rp. 100.000 have a medium spending frequency (4-6 times) is relatively small at 3%, expenditures at Rp. 100.000 to less than Rp. 500.000 have occasionally frequency (1-3 times) most dominating by 31%, and expenditures at Rp. 500.000 to less than Rp. 1.000.000 have medium frequency (4-6 times) most dominating by 14%.